2022
DOI: 10.1007/s00203-022-03314-w
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of probiotics in eradication therapy of Helicobacter pylori

Abstract: Helicobacter pylori (H. pylori) is a well-known pathogen that infects approximately half of the world’s population. It is a pathogenic agent with potential health hazards related to diverse diseases, especially digestive diseases, such as chronic gastritis, peptic ulcer, and gastric carcinoma. In clinical, antibiotics are commonly applied in eradication therapy of H. pylori. However, the increase in antibiotic resistance and side effects has induced the failure of eradication therapy. Recent studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 139 publications
0
13
0
2
Order By: Relevance
“…Several studies have reported that traditional H. pylori eradication treatments have less than 80% effectiveness, while their use comes with the side effects associated with antibiotics’ use [ 61 ]. Some recent studies report that the application of specific probiotic treatments may improve the efficacy and resistance of H. pylori treatment [ 24 ]. A meta-analysis of randomized controlled trials concluded that, during H. pylori eradication therapy, the administration of probiotics may improve the degree of eradication, reducing the incidence of treatment adverse effects and alleviating clinical symptoms associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that traditional H. pylori eradication treatments have less than 80% effectiveness, while their use comes with the side effects associated with antibiotics’ use [ 61 ]. Some recent studies report that the application of specific probiotic treatments may improve the efficacy and resistance of H. pylori treatment [ 24 ]. A meta-analysis of randomized controlled trials concluded that, during H. pylori eradication therapy, the administration of probiotics may improve the degree of eradication, reducing the incidence of treatment adverse effects and alleviating clinical symptoms associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding current trends on the different uses of biotics in diseases, the present review highlighted a variety of important fields, such as the administration of probiotics in the context of acute infectious diarrhea [ 17 , 51 , 52 ], nosocomial diarrhea [ 20 , 21 , 52 , 57 ], diarrhea associated with antibiotics [ 22 , 23 , 51 , 53 , 59 , 60 ], functional abdominal pain [ 53 , 64 ], pouchitis [ 53 ], and necrotizing enterocolitis in infants [ 53 ], as well as their role as adjuncts in ulcerative colitis [ 52 ], in the improvement in the eradication rate of H. pylori [ 24 , 25 , 26 ], and as prevention tools for allergic disease in infants [ 34 , 37 ]. Emerging fields include neurodevelopmental disorders [ 36 , 37 , 38 ], obesity [ 40 ], otitis media [ 42 ], and viral respiratory infections [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…7B ). The use of probiotics is sometimes shown to have a positive effect on species diversity following H. pylori infection ( 65 , 66 ). Thus, in addition to the capacity of AMPs and gAMPs to eliminate H. pylori , another benefit of the engineered probiotic treatments may lie in the probiotic itself, not in its capacity to control H. pylori ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given the global rise in antibiotic resistance and the limitations of the STT, there is an urgent need to explore adjunctive therapies that can enhance eradication rates. Probiotics represent a promising avenue, but their specific role and mechanisms in improving treatment outcomes remain understudied and require comprehensive investigation [111].…”
Section: Need For Improved Treatment Strategiesmentioning
confidence: 99%